2015
DOI: 10.5539/gjhs.v7n6p129
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Nurses Regarding Organ Donation

Abstract: Introduction:Treatment team charged to help patients and their family making decision about donate organs in the final stage of life. Hence, their knowledge and attitude is important to plan of increasing the rate of organ donation.Materials and Methods:About 150 nurses recruited in this cross-sectional study randomly. After taking informed consent, questionnaires were filled. The data collection tool was a multipart questionnaire including demographic information, 18 questions about attitude and practice and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Symvoulakis et al (), showed that 25% of their participants believed that being in possession of a donor card was like tempting death. Similarly, in Babaie et al ’s () study, 78% of those who did not have a donor card thought that if a person had previously expressed the wish to donate, in a life‐critical situation, resuscitation measures would not be used or death would be prematurely declared. These data revealed that although there is confidence in the health system, a small proportion of the population, including some nurses, maintains these unfounded beliefs.…”
Section: Discussionmentioning
confidence: 96%
“…Symvoulakis et al (), showed that 25% of their participants believed that being in possession of a donor card was like tempting death. Similarly, in Babaie et al ’s () study, 78% of those who did not have a donor card thought that if a person had previously expressed the wish to donate, in a life‐critical situation, resuscitation measures would not be used or death would be prematurely declared. These data revealed that although there is confidence in the health system, a small proportion of the population, including some nurses, maintains these unfounded beliefs.…”
Section: Discussionmentioning
confidence: 96%
“…It is so, as the authors suggest, because nurses with a negative attitude towards organ donation can influence people who are exposed to the subject, or generate distrust in the process [25]. Another study states that nurses who have a positive attitude have a better practice when it comes to organ donation related tasks [26].…”
Section: Discussionmentioning
confidence: 99%
“…The transplant coordinator is valued; however, a lack of professional definition and educational preparation has created confusion regarding the role [27]. It is important to include curricular training that addresses the donation of organs in nursing [28]. The authors of the present study believe that NTCs should be considered as Advanced Practice Nursing (APN).…”
Section: Discussionmentioning
confidence: 96%